2016
DOI: 10.1515/zpch-2016-0806
|View full text |Cite
|
Sign up to set email alerts
|

Photo-CIDNP in the Reaction Center of the Diatom Cyclotella meneghiniana Observed by 13C MAS NMR

Abstract: Photo-CIDNP in the reaction center of the diatom Cyclotella meneghiniana observed by 13 C MAS NMRThe solid-state photo-CIDNP effect in a new kingdom of the tree of life Abstract: Photo-CIDNP MAS NMR presents a unique tool to obtain insight into the photosynthetic reaction centers (RCs) of bacteria and plants. Using the dramatic enhancement of sensitivity and selectivity of the solid-state photo-CIDNP effect, structural as well as functional information can be obtained from the cofactor molecules forming a ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(74 citation statements)
references
References 69 publications
3
71
0
Order By: Relevance
“…The data imply that the sign change is most probably due to a decrease of the extent of the DR which is itself caused by a shorter-lived molecular triplet state at higher field which is quenched, if there is a carotenoid nearby. A previous work on PS I core complexes showed that the DR mechanism is not active or contributes only very slightly to the total nuclear spin polarisation leading to typically emissive signals (Zill et al 2017b). It was shown that the extent of the effect is increasing with decreasing magnetic field (Thamarath et al 2012).…”
Section: The Origin Of the Sign-change Of Many Light-induced Signals mentioning
confidence: 95%
See 3 more Smart Citations
“…The data imply that the sign change is most probably due to a decrease of the extent of the DR which is itself caused by a shorter-lived molecular triplet state at higher field which is quenched, if there is a carotenoid nearby. A previous work on PS I core complexes showed that the DR mechanism is not active or contributes only very slightly to the total nuclear spin polarisation leading to typically emissive signals (Zill et al 2017b). It was shown that the extent of the effect is increasing with decreasing magnetic field (Thamarath et al 2012).…”
Section: The Origin Of the Sign-change Of Many Light-induced Signals mentioning
confidence: 95%
“…The most deshielded signal appears emissively at 192.1 ppm and can be assigned to a carbon at the 13 1 -position of Chl a. The signal resonates at the same position like a donor Chl a observed in PS I of the diatom C. meneghiniana (Zill et al 2017b) and the signal is also observed in PS II of P. tricornutum (see chapter 3.3.1), which does not allow to assign this signal to a specific cofactor. The emissive resonance at 168.3 ppm can be assigned to a C-19 position and is most suitable for a Chl a cofactor.…”
Section: Signal Assignments Of the 13 C Photo-cidnp Mas Nmr Spectra Omentioning
confidence: 98%
See 2 more Smart Citations
“…The high sensitivity and selectivity of the photo-CIDNP MAS NMR experiment provide an excellent analytical tool for studying photosynthetic SCRPs in great detail (29,30). This method has been applied to various photosynthetic systems (31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%